Collaboration and Co-Production of Knowledge in Healthcare: Opportunities and Challenges - Jo Rycroft-Malone; Christopher R. Burton; Tracey Bucknall; Ian D. Graham; Alison M. Hutchinson; Dawn Stacey (Kerman University of Medical Sciences, 2016)
Over time there has been a shift, at least in the rhetoric, from a pipeline conceptualisation of knowledge implementation, to one that recognises the potential of more collaboration, co-productive approaches to knowledge production and use. In this editorial, which is grounded in our research and collective experience, we highlight both the potential and challenge with collaboration and co-production. This includes issues about stakeholder engagement, governance arrangements, and capacity and capability for working in a coproductive way. Finally, we reflect on the fact that this approach is not a panacea, but is accompanied by some philosophical and practical challenges.